Korelasi Kepemimpinan dan Perilaku Etis Kepala Sekolah dengan Motivasi Kerja dan Kinerja Guru SMP Pius Tegal - Dewi Apriani; Mustika Dewi Maria; A Rony Yulianto (Cakrawala: Jurnal Pendidikan, 2017)
This study aimed to determine the relationship of principal leadership with teacher work motivation; Principal ethical behavioral relationship with teacher work motivation; Leadership relationships and principal ethical behavior with teacher work motivation; And the relationship of work motivation with teacher performance. Subjects of this study were 20 teachers. The implications are: 1) Principal is expected to lead and coordinate all activities in school thus results can be felt directly by teachers to improve their work motivation. 2) Principal’s ethical attitudes and actions make teachers feel cared for and respected, thus improving great passion to work. 3) Teacher’s work motivation cannot be used as a indicator to improve teacher’s performance, but work motivation can be directed to improve work productivity in school